INVENTARISASI ANGGREK DI HUTAN BUKIT LAWANG DESA TIMBANG JAYA KECAMATAN BAHOROK KABUPATEN LANGKAT - Syaiful Azhar; Muhammad Iqbal H Tambunan; Yusran Efendi Ritonga (Universitas Islam Negeri Sumatera Utara, 2021)
Indonesia has 25% of the world's flowering plant species. One of the largest flowering plants in Indonesia is the Orchidaceae family. There are 4,000 – 5,000 species of orchids scattered in various provinces, one of which is in North Sumatra. There is still little information about the Family Orchidaceae found in the Bukit Lawang Forest, the purpose of this research is to determine the types of orchids found in the Bukit Lawang Forest, Timbang Jaya Village, Bahorok District. This research was conducted from December 2020 to January 2021. The research method is exploratory by making an inventory of the types of orchids found along the exploration path. The results found 9 species of orchids (7 genera) consisting of 7 epiphytes and 2 terrestrial, namely Bulbophyllum sp., Bromheadia sp., Plocoglottis sp., Epidendrum sp., Pinalia sp., Dendrobium sp. and Dendrobium lobolatum.